Heidegger, Spengler och autentisk fascism (Sociologisk Forskning, 2006)
This article is an attempt to make our understanding of fascism more comprehensive. By focusing Heideggers short texts from 1933 and relating them to his other writings it is shown that he hoped that the German National Socialism would be much more radical than it really was. Thus, we can see him as an example of ”authentic fascism” which came in conflict with Realfascismus.
Keywords: Martin Heidegger; Oswald Spengler; fascism; conservative revolution; palingenetic ultranationalism